2004
DOI: 10.1111/j.1399-543x.2004.00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of insulin glargine in children and adolescents with type 1 diabetes

Abstract: This retrospective study suggests that glargine is at least as effective as other long-acting insulins but that care must be taken during the conversion process to avoid hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 18 publications
0
36
0
2
Order By: Relevance
“…The strong bias seen for insulin aspart is not due to access, with identical open access to all options in both countries, or supported by the available literature, which suggests comparable pharmacokinetic/pharmacodynamic properties across the three available rapid‐acting analogues . In contrast, the dominance of glargine is unsurprising, being the only readily available truly once‐daily basal insulin option due to its smooth long‐acting plasma concentration profile for many years now, in addition to the purported potential benefits in hypoglycaemia, irrespective of timing of injection . It is also possible that choice of insulin reflects some form of pharmaceutical bias or simply the historical order that new analogues became available locally, with clinicians persisting with established insulin choices.…”
Section: Discussionmentioning
confidence: 99%
“…The strong bias seen for insulin aspart is not due to access, with identical open access to all options in both countries, or supported by the available literature, which suggests comparable pharmacokinetic/pharmacodynamic properties across the three available rapid‐acting analogues . In contrast, the dominance of glargine is unsurprising, being the only readily available truly once‐daily basal insulin option due to its smooth long‐acting plasma concentration profile for many years now, in addition to the purported potential benefits in hypoglycaemia, irrespective of timing of injection . It is also possible that choice of insulin reflects some form of pharmaceutical bias or simply the historical order that new analogues became available locally, with clinicians persisting with established insulin choices.…”
Section: Discussionmentioning
confidence: 99%
“…Pump studies have shown that younger children often need more basal insulin before midnight than after (reversed dawn phenomenon). With a basal/bolus analog regimen this can be achieved by giving regular instead of rapid acting insulin for the last bolus of the day (night time blood glucose levels need to be checked) …”
Section: Dawn Phenomenonmentioning
confidence: 99%
“…Others have found an overall reduction in the number of episodes of hypoglycaemia in this age group. [62][63][64] There are limited published data on clinical effects of insulin Detemir in the paediatric age range, due to the recent market availability, but studies in adult populations have suggested a reduction in nocturnal hypoglycaemia, 47 65 66 and it is likely that this may be replicated in children.…”
Section: Clinical Utilitymentioning
confidence: 99%